Impacto de la industria pesquera sobre el sistema marino litoral de puerto malabrigo; mayo - diciembre del 2003 - Vásquez García, Antero Celso (2005)
The impact of the fishing industry was evaluated in the coastal marine system of Puerto Malabrigo; Rázuri district, Ascope county; Region LA Libertad from May to December 2003. Four sampling stations were settled down, 1: 500 meters at south of the jetty, 2: Betwen snub and borders in front of SIPESA plant; 3: Betwen snub and borders in front of HAYDUCK SAC plant, 4: At one Km at north of the station 3. Samples of surface water and bottom, as well as of silts, were took and they analyzed following the methodology suggested in the annexes 1, 2 and 3 of the Ministerial Resolution Nº. 0032002-PE (Protocol for the drain pursuit and receiving marine body of 2002-04-13). Total and fecal Coliforms x 100 ml; were determined by the Normalized Methods of the Analysis of Drinkable and Residual Waters 9215 A, 9221 A, 9221 B, 9221 C described by APHA; AWWA and WPCF (1989). It was concluded that: 1. The fishing industry generates negatives environmental impacts valued as significant and very significant on the coastal marine system of Puerto Malabrigo; 2. Significant positive impacts were generated in populational aspects of education and economy by the employment generation, the increment of the level of personal remuneration and of economic resources for the Rázuri Distrital Municipality; 3. Polychaets of the genera Nereis, Diopatra and Chaethopterus, were indicators of environmental impacts of the fishing industry on the coastal marine system of Puerto Malabrigo.